PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA MENULIS PERMULAAN DENGAN ACTIVE LEARNING DI SEKOLAH DASAR KAWASAN MISKIN *) - Andayani, Andayani (STILISTIKA, 2012)
PENGEMBANGAN MODEL  PEMBELAJARAN MEMBACA MENULIS PERMULAAN DENGAN ACTIVE LEARNING  DI SEKOLAH DASAR KAWASAN MISKIN  *)AndayaniProgram Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Sebelas Maret Surakarta Jl. Ir. Sutami No. 1 Kentingan Surakarta Ponsel: 08164270281 Pos-El: bu_anda09@yahoo.co.id AbstractThis research was aimed at presenting an instructional model to improve elementary reading-writing  at the primary school with activelearning approach, which has been an instruction of reading-writting science noted by the presentation this to the primary school students. This has made the a difficult and uninteresting subject.  The results of the research were as follows. Firstly, based on the phase of preliminary research, the models of teaching with active learning approach is required by the teachers and shall be fulfilled immediately. The students, furthermore, require elementary reading-writing instruction which is easily followed and exciting. Secondly, the phase of development results in an effort of creating a elementary reading-writing instruction at the primary school by applying various instructions  and instructional media, and by making the teachers understand that. Thirdly, the significance is known from the comparison between their pre-test and their post-test scores. The response of the decision, makers and the response of the teachers are positive. There are can generate great benefits for a sustainable application of the atrractive approach instruction in the future.Kata Kunci: model, pembelajaran, membaca-menulis, active learning.